2001
DOI: 10.1159/000055356
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Significance of Cathepsin D Expression in Gastric Adenocarcinoma

Abstract: Objective: An estrogen-regulated lysosomal protease, cathepsin D, has been detected in a variety of tissues. This proteinase has been described as closely associated with tumor progression and metastasis in malignant tumors. The purpose of this study was to determine the clinicopathological and prognostic significance of cathepsin D expression in gastric adenocarcinoma. Methods: In a consecutive series of 478 patients with gastric carcinoma (median follow-up period: 93 months, range: 1–285 months), cathepsin D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…There was a strong correlation between high CD expression in carcinomas of the M and SM. These results support previous studies in gastric adenocarcinomas that found a significant association between CD expression and the depth grading of tumor invasion 15,16) In addition, a correlation between CD expression and prognosis was reported in oesophageal squamous cell carcinoma 1') and breast carcinoma 6.'.1s). However, until now a similar association in colorectal tumors has not been confirmed s-11~.…”
Section: Discussionsupporting
confidence: 91%
“…There was a strong correlation between high CD expression in carcinomas of the M and SM. These results support previous studies in gastric adenocarcinomas that found a significant association between CD expression and the depth grading of tumor invasion 15,16) In addition, a correlation between CD expression and prognosis was reported in oesophageal squamous cell carcinoma 1') and breast carcinoma 6.'.1s). However, until now a similar association in colorectal tumors has not been confirmed s-11~.…”
Section: Discussionsupporting
confidence: 91%
“…Cathepsin D immunohistochemical expression has also been assessed in a variety of tumours, such as gastric adenocarcinomas (11), colorectal carcinomas (12), lung adenocarcinomas and breast carcinomas (13, 14, 25, 26). Particularly in the case of breast carcinomas, some authors have reported that stromal expression of cathepsin D, together with E‐cadherin and lack of estrogen receptors, is considered an important prognostic factor, especially in lymph node‐negative patients (27), is an indicator of prognosis and metastasis from an early stage (26), and is positively correlated with tumour grade.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that cathepsin D has a relation with prognostic parameters like advanced tumor stage, 9 poor malignancy grade, 9,26 development of clinical metastasis, 7,27 depth of tumor invasion, 28,29 and was also reported to have increased intensity of expression in the advancing front of the lesion. 13,30 These observations which link increased cathepsin D expression to parameters reflective of a poorer grade of carcinoma were similar to our findings.…”
Section: Discussionmentioning
confidence: 99%